2006
DOI: 10.1007/s11224-006-9006-4
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective protection of hydantoins – essential for hydantoin based anti-epileptic drugs

Abstract: The synthesis and NMR elucidation of six novel mono-and bis-Boc protected hydantoins are reported. The hydantoins 5-methylhydantoin, 5,5-dimethylhydantoin and a pentacycloundecane hydantoin exhibit an increase in substitution and steric hindrance at C-5. Kinetic and reagent controlled monoprotection of the smaller hydantoins achieve regioselective protection at N-1 while the bulky cage hydantoin is protected at N-3 . Hydantoin based anti-epileptic drugs such as 5,5-diphenylhydantoin require regioselective subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Kruger and Mdluli [71] in the next paper describe investigation of regioselective protection of hydantoins for the purpose of understanding the activity of the nitrogen atoms on hydantoin rings. Hydantoins can be applied as anti-epileptic drugs and 5,5-diphenylhydantoin is well known also for its anticonvulsant activity [72][73][74].…”
Section: Issuementioning
confidence: 99%
“…Kruger and Mdluli [71] in the next paper describe investigation of regioselective protection of hydantoins for the purpose of understanding the activity of the nitrogen atoms on hydantoin rings. Hydantoins can be applied as anti-epileptic drugs and 5,5-diphenylhydantoin is well known also for its anticonvulsant activity [72][73][74].…”
Section: Issuementioning
confidence: 99%
“…in dry N,N-dimethylformamide in the presence of potassium carbonate as ab ase [1,2]. The heterogeneous solution was heated at 85°Cfor six hours and concentrated in vacuo.…”
Section: Source Of Materialsmentioning
confidence: 99%
“…However, the emergence of a range of standard 2D NMR techniques has helped a great deal in overcoming these problems. Our group has successfully used 2D NMR techniques to elucidate numerous PCU derivatives [12][13][14][15][16][17][18][19][20][21]. Odisitse et al [22] recently reported potent anti-inflammatory activity for the PCU diamine 9; this discovery led to the design and synthesis of compounds 3-8 which are currently being investigated as potential inflammatory agents while compounds 1 and 2 are precursors to 3 and 4. triethylamine was refluxed under nitrogen for 36 h to obtain the novel compounds 18 and 19.…”
Section: Introductionmentioning
confidence: 99%